'What's on your Bucket List?': Tourism, identity and imperative experiential discourse. (November 2017) - Thurnell-Read, Thomas
Highlights: Examines the 'Bucket List' concept in relation to tourism experiences. Uses Critical Discourse Analysis to analyse Bucket List use and content. Shows Bucket Lists used to define worthy and desirable tourism experiences. Introduces the concept of imperative experiential discourse. Bucket Lists informed by economic, cultural and symbolic capital. Abstract: The concept of the Bucket List has achieved rapid and widespread recognition. This article makes an original Critical Discourse Analysis of the Bucket List as a cultural phenomenon that provides important insights into the interrelation between identity and tourism. The Bucket List is used to communicate specific suggestions of desirable tourism experiences and uses what can be termed the experiential imperative discourse, where the language, tone and framing of the text positions the experience described as essential and obligatory. Ultimately, the Bucket List discourse serves to prescribe culturally specific ideas of what constitute 'good' tourism experiences and is imposed on individuals who are prompted to desire a constantly renewing range of tourism experiences.